Unveiling the anti-cancer potential of Euphorbia greenwayi: cytotoxicity, cell migration, and identification of its chemical constituents - Ahmed A. Zaghlol; Zeinab A. Kandil; Miriam F. Yousif; Riham Salah EL-Dine; Wafaa M. Elkady (SpringerOpen, 2024)
Abstract Background Different herbal phytochemicals have potential in cancer treatment, Euphorbia genus has valuable secondary metabolites and is used in traditional medicine to treat various ailments. However, the specific constituents and biological activity of Euphorbia greenwayi remain largely unexplored. Results Euphorbia greenwayi aerial parts were extracted using methanol. Consequently, the methanol extract was then fractionated with solvents of different polarities viz., n-hexane, chloroform, and ethyl acetate. All were screened for their cytotoxic activity against different cell lines; MCF-7, HepG-2, and SW620. The n-hexane (HF) and chloroform (CF) fractions showed considerable activity against all tested cell lines especially MCF-7 with IC50 values at 18.6 ± 0.2 and 17.5 ± 0.6 μg/ml respectively. Therefore, a cell migration assay on the MCF-7 cell line was applied to both fractions as well as investigation and isolation of the main active constituents. Lupeol, β-sitosterol, and cycloartenol were isolated from the nonpolar fractions of E. greenwayi for the first time. Conclusions Euphorbia greenwayi aerial parts exhibit considerable anti-cancer effects via cytotoxicity. Three chemical constituents with promising cytotoxic activity are identified.